Mapping dynamic working life patterns and the impact of occupational exposures: a scoping review - Rachel Louise Hasting; Karen Marieke Oude Hengel; Taina Leinonen; Ute Bültmann; Ingrid Sivesind Mehlum; Alex Burdorf; Michelle C Turner; Laura Salonen; Damien M McElvenny; Svetlana Solovieva (BMC Public Health)
Abstract Background An ageing population and increasing life expectancy has intensified pressure to prolong working lives among high-income countries. Emerging research has sought to characterise dynamic working life patterns (how labour market participation changes over the working career), and how various factors, including occupational exposures, influence these patterns. This scoping review aims to systematically map the literature in this area and to identify future research needs. Methods A systematic search was carried out in PubMed, Embase, Web of Science and Scopus. Original studies were included if they included individuals from the general working-age population (defined as 18–70 years of age) or from patient-, sector-, industry-, or occupation-specific populations, and if they examined associations between at least one occupational exposure and a measure of dynamic working life patterns, grouped into either labour market participation trajectories or cumulative time spent in various labour market states. Studies were considered too heterogeneous to allow for quantitative synthesizing of results or calculation of an average measure of working life patterns across studies by exposure. Results The seventeen included original studies were heterogenous with regards to study populations, analysis methods, occupational exposures, and outcomes. Studies of biomechanical and psychosocial exposures were the most common, with indications that biomechanical factors are associated with reduced work participation. Conclusions Future studies would benefit from clearer definitions of occupational exposures and measures of dynamic working life patterns, a broader inclusion of occupational exposures, and measures of cumulative exposure.